CD98 as a novel prognostic indicator for patients with stage III/IV hypopharyngeal squamous cell carcinoma. Issue 11 (1st August 2014) - Toyoda, Miroru; Kaira, Kyoichi; Shino, Masato; Sakakura, Koichi; Takahashi, Katsumasa; Takayasu, Yukihiro; Tominaga, Hideyuki; Oriuchi, Noboru; Nikkuni, Osamu; Suzuki, Masami; Iijima, Misa; Tsukamoto, Norifumi; et al.
Abstract Background Both L‐type amino acid transporter 1 (LAT1) and CD98 are strongly expressed in primary human cancer and play essential roles in tumor growth. We studied the clinicopathological significance of LAT1 and CD98 expression in hypopharyngeal squamous cell carcinoma (SCC). Methods A total of 70 patients with stage III/IV disease were retrospectively reviewed. Immunohistochemical staining of tumor sections was used to examine LAT1, CD98, Ki‐67, CD34, and p53. Results High LAT1 and CD98 expression were noted in 60.0% and 47.1%, respectively (p = .174). A statistically significant correlation was recognized between LAT1 and CD98 expression and both expressions were closely associated with tumor cell proliferation. Although LAT1 expression was not significantly associated with poor survival, multivariate analysis revealed high CD98 expression to be an independent prognostic factor for predicting a poor outcome. Conclusion CD98 is a promising prognostic marker for predicting outcomes after surgical treatment in patients with advanced hypopharyngeal SCC. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1569–1574, 2015